CORONIS - International study of caesarean section surgical techniques: The follow-up study - Abalos, E; Oyarzun, E; Addo, V; Sharma, J; Matthews, J; Oyieke, J; Masood, SN; Sheikh, E; Brocklehurst, B; Farrell, F; Gray, S; Hardy, P; et al. (2013)
Background: The CORONIS Trial was a 2×2×2×2×2 non-regular, fractional, factorial trial of five pairs of alternative caesarean section surgical techniques on a range of short-term outcomes, the primary outcome being a composite of maternal death or infectious morbidity. The consequences of different surgical techniques on longer term outcomes have not been well assessed in previous studies. Such outcomes include those related to subsequent pregnancy: mode of delivery; abnormal placentation (e.g. accreta); postpartum hysterectomy, as well as longer term pelvic problems: pain, urinary problems, infertility. The Coronis Follow-up Study aims to measure and compare the incidence of these outcomes between the randomised groups at around three years after women participated in the CORONIS Trial.Methods/Design: This study will assess the following null hypotheses: In women who underwent delivery by caesarean section, no differences will be detected with respect to a range of long-term outcomes when comparing the following five pairs of alternative surgical techniques evaluated in the CORONIS Trial:. 1. Blunt versus sharp abdominal entry. 2. Exteriorisation of the uterus for repair versus intra-abdominal repair. 3. Single versus double layer closure of the uterus. 4. Closure versus non-closure of the peritoneum (pelvic and parietal). 5. Chromic catgut versus Polyglactin-910 for uterine repair. The outcomes will include (1) women's health: pelvic pain; dysmenorrhoea; deep dyspareunia; urinary symptoms; laparoscopy; hysterectomy; tubal/ovarian surgery; abdominal hernias; bowel obstruction; infertility; death. (2) Outcomes of subsequent pregnancies: inter-pregnancy interval; pregnancy outcome; gestation at delivery; mode of delivery; pregnancy complications; surgery during or following delivery.Discussion: The results of this follow-up study will have importance for all pregnant women and for health professionals who provide care for pregnant women. Although the results will have been collected in seven countries with limited health care resources (Argentina, Chile, Ghana, India, Kenya, Pakistan, Sudan) any differences in outcomes associated with different surgical techniques are likely to be generalisable throughout the world.Trial registration: ISRCTN31089967. © 2013 The CORONIS Collaborative Group; licensee BioMed Central Ltd.